Roald Amundsen's Belgica diary : the first scientific expedition to the Antarctic - Amundsen, Roald; Decleir, Hugo (Red.) (Bluntisham Books, 1999)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; Sydpolen; dagbok; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Bernt Balchen : polar aviator - Glines, Carroll V (Smithsonian Institution Press, 1999)
Keywords: Antarktis; Sydpolen; Sydpolflyvningen; Sydpolsekspedisjonen; biografier; ekspedisjoner; fly; luftfart; polarekspedisjoner; polarflyving

Scott and Amundsen - Honda, Katuiti (The Asahi-Shinbun, 1999)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; biografier; ekspedisjoner; polarforskning; polarområdene

Antarktis - Killie, Barbro; Savinova, Tatiana; Kleivane, Lars; Lie, Elisabeth; Skaare, Janneche Utne; Nygård, Torgeir (Miljøgifter og radioktivitet i norsk fauna: inkludert Arktis og Antarktis, 1999)
Keywords: Antarktis; biologi; forurensning; zoologi

Miljøgifter og radioaktivitet i norsk fauna : inkludert Arktis og Antarktis - Knutzen, Jon; Fjeld, Eirik; Hylland, Ketil; Killie, Barbro; Kleivane, Lars; Lie, Elisabeth; Nygård, Torgeir; Savinova, Tatiana; Skåre, Janneche Utne; Aanes, Karl Jan (Direktoratet for naturforvaltning, 1999)
Keywords: Antarktis; dyreliv; forurensning; miljøgifter; polarområdene; radioaktivitet; toksikologi; zoologi

Akkumulering av tungmetaller i en antarktisk næringskjede - Lie, Elisabeth; Nygård, Torgeir; Røv, Nils; Steinnes, Eiliv (NINAs strategiske instituttprogrammer 1991-95. Forurensningsøkologi. Sluttrapport, 1999)
Keywords: Antarktis; antarktispetrell; forurensning; krill; miljøgifter; næringskjede; sjøfugler

Impact of recent climate on glacier mass balance : studies on Kongsvegen, Svalbard and Jutulstraumen, Antarctica - Melvold, Kjetil (University of Oslo, 1999)
Keywords: Antarktis; akkumulasjon; geografi; glasiologi; isbreer

Polare jubileer i 1997 og 1998 - Barr, Susan (Polarboken, 1998)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie

The Floating Factory: Dominant Designs and Technological Development of Twentieth-CenturyWhaling Factory Ships - Basberg, Bjørn L (The Northern Mariner/Le Marin du nord, 1998)
Keywords: Antarktis; historie; hvalfangere; hvalfangst; hvalkokeri

Estimate of the subglacier dielectric constant of an ice shelf using a ground-penetrating step-frequency radar - Hamran, Svein Erik; Erlingsson, Bjørn; Gjessing, Yngvar; Mo, Per (IEEE Transactions on Geoscience and Remote Sensing, 1998)
The mass balance of the Antarctic ice cap, its stability, and the role of the surrounding ice shelf in bottomwater mass formation is, to a large extent, dictated by processes associated with subsurface freezing and melting, where the submerged ice meets the surrounding ocean. It is demonstrated how multifrequency ground-penetrating radar data collected at the Riiser-Larsenisen can be used to examine the physical conditions of the ice-shelf subsurface. The received radar signal from three different frequency intervals, 10-30, 155-170, and 330-360 MHz (range of wavelengths from 15 to 0.5 m in the ice), was analyzed by using a plane reflector model. It is demonstrated that the data can be successfully used to distinguish between types of ice at the ice-ocean interface, such as for freezing marine ice, melting marine ice, melting meteoric ice from the ice cap, and melting firn/ice. The data analysis shows that the subsurface can be regarded as rough on length scales in the order of 1 m.
Keywords: Antarktis; brehylle; fjernanalyse; geofysikk; georadar; glasiologi; isbreer; isbrem; isshelf; oseanografi

Noruega y las regiones polares - Hansson, Rasmus (Real Ministerio Noruego de Asuntos Exteriores, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norvegija i poljarnye rajony - Hansson, Rasmus (Izdano Ministerstvom inostrannych del Norvegii, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norwegen und die Polargebiete - Hansson, Rasmus (Kgl. Norwegisches Ministerium für Auswärtige Angelegenheiten, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

I helters spor : Sydpolsekspedisjonens kulturelle organisasjon - Murvold, Hilde Karin (Universitetet i Bergen, 1998)
Keywords: Antarktis; Sydpolen; Sydpolsekspedisjoner; ekspedisjoner; etnologi; kultur

Tvers over Antarktis alene - Ousland, Børge (Polarboken, 1998)
Keywords: Antarktis; ekspedisjoner

The effects of personality and interpersonal relations on crew performance during space simulation studies - Sandal, Gro Mjeldheim (Life Support & Biosphere Science, 1998)
There has been a substantial increase in the number of people living and operating in isolated, confined, and artificially engineered environments, such as spacecraft, deep diving, weather stations, submarines, and polar outposts. This article gives an overview of research undertaken in a variety of extreme environments in an effort to better understand how semiautonomous, task-oriented groups operating within these environments develop over time, as well as identification of the individual characteristics that promote performance under such circumstances. Research reviewed includes space simulation studies for the European Space Agency (ESA) where groups were isolated in hyperbaric chambers, as well as findings from polar expeditions, space missions, submarine missions, and other military settings. Findings from the space simulation studies in hyperbaric chambers provided empirical evidence for interpersonal issues anecdotally reported in Antarctica and in other isolated, operational team environments, such as "scapegoating" of deviant crew members, displacement of aggression to outside personnel, and time patterns in psychological reactions. No indications of a "psychological limit" for how long people can tolerate remaining in isolation and confinement were found. Certain personality characteristics were consistently associated with coping, and individuals characterized by strong achievement motivation combined with interpersonal sensitivity seemed to adapt better than others. Together, these results have implications for selection and training of people operating within extreme environments.
Keywords: Antarktis; polarekspedisjoner; polarforskere; polarområdene; psykologi

Expedition photography in polar areas - Barr, Susan (Photoresearcher, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; fotografi; historie; polarekspedisjoner; polarområdene

Scott und Amundsen - Barr, Susan (Arktis Antarktis, 1997)
Keywords: Antarktis; ekspedisjoner; historie

In To the South Pacific and On To Antarctica - Feeney, Robert E (Polar journeys : the role of food and nutrition in early exploration, 1997)
Keywords: Antarktis; Belgica ekspedisjon; Frederick Cook; Roald Amundsen; ernæring; mat; oppdagelsesreiser

The Quest for the South Pole: Successes and Deaths - Feeney, Robert E (Polar journeys : the role of food and nutrition in early exploration, 1997)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ernæring; mat; oppdagelsesreiser

Strategi for norsk forskning i Antarktis - forskningsråd, Norges (Norges forskningsråd, 1997)
Keywords: Antarktis; Antarktistraktaten; Norge; forskning; forvaltningsansvar; miljøendringer; polarområdene

Indentation testing on ice from the Filchner Ronne Ice Shelf area, Antarctica: preliminary results - Gerland, Sebastian (Filchner-Ronne Ice Shelf Programme. Report, 1997)
Keywords: Antarktis; Sørishavet; glasiologi; havis

Dagboksnotater fra Sydpolen - Hassel, Sverre (Vågemot miniforl., 1997)
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; polarområdene

Belgica-ekspedisjonen : et hundreårsminne - Lie, Svein B (Norvegiana Nytt, 1997)
Keywords: Antarktis; Belgica ekspedisjon; forskning; oppdagelsesreiser; polarekspedisjoner

Sydpolen, fra drøm til virkelighet - Arnesen, Liv (Polarboken, 1996)
Keywords: Antarktis; ekspedisjoner

Et eksperiment i egenmestring - Pedersen, Cato Zahl (Polarboken, 1996)
Keywords: Antarktis; ekspedisjoner

Governing the Antarctic : the effectiveness and legitimacy of the Antarctic Treaty System - Støkke, Olav Schram (ed.); Vidas, Davor (ed.) (Cambridge University Press, 1996)
Keywords: Antarktis; Antarktistraktaten 1959; internasjonal politikk; polarområdene; politikk

The final report of the Fridtjof Nansen Institute on the International Antarctic Regime Project (Fridtjof Nansens institutt, 1995)
Keywords: Antarktis; forskning

Background to the establishment of Norsk Polarinstitutt : postwar scientific and political agendas - Friedman, Robert Marc (Umeå university, 1995)
Keywords: Antarktis; Norsk Polarinstitutt; historie; internasjonal; polarområdene; politikk

Akkumulering av tungmetaller i en antarktisk næringskjede : hovedoppgave i naturmiljøkjemi - Lie, Elisabeth (Universitetet i Trondheim, 1995)
Keywords: Antarktis; antarktispetrell; forurensning; krill; miljøgifter; næringskjede; sjøfugler

Accumulation of heavy metals in an Antarctic food-chain - Lie, Elisabeth; Steinnes, Eiliv ([Heavy Metals Secretariat], 1995)
Keywords: Antarktis; forurensning; miljøgifter; næringskjede

Reproductive effort in the Antarctic petrel Thalassoica antarctica : the effect of parental body size and condition - Lorentsen, Svein-Håkon (Norwegian Institute for Nature Research (NINA), 1995)
Keywords: Antarktis; fugler; ornitologi; petreller; reproduksjon; zoologi

Two further bipolar lichens - Øvstedal, Dag Olav; Gremmen, Niek J M (Graphis scripta, 1995)
Keywords: Antarktis; botanikk; lav; planter

The Vestfold Hills: the Norwegian connection - Patterson, D (ANARE News, 1995)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Sydpolekspedisjoner (Polarboken, 1994)
Keywords: Antarktis; ekspedisjoner

Before the heroes came : Antarctica in the 1890s - Baughman, Timothy H (University of Nebraska Press, 1994)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; oppdagelsesreiser; polarhistorie

Teltet på Sydpolen - Dannevig, Alv (Vær & klima, 1994)
Keywords: Antarktis; ekspedisjoner; logistikk

The legitimacy of the Convention on the on the Regulation of Antarctic Mineral Resource Activities - Joyner, Christopher C (Fridtjof Nansens institutt, 1994)
Keywords: Antarktis; jus; mineraler

Alene til Sydpolen - Kagge, Erling (Polarboken, 1994)
Keywords: Antarktis; ekspedisjoner

The protocol on environmental protection to the Antarctic Treaty: the question of effectiveness - Orrego Vicuña, Francisco (Fridtjof Nansens institutt, 1994)
Keywords: Antarktis; jus; miljøvern

The Antarctic Treaty system and Antarctic tourism: towards a legal regime? - Vidas, Davor (International Challenges, 1994)
Keywords: Antarktis; jus; turisme

Executive summary: International Antarctic Regime Project publication series 1993 (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus; litteratur; politikk

Moje życie polarnika - Amundsen, Roald; Thylwe, Halina (Iskry, 1993)
Keywords: Antarktis; biografi; ekspedisjoner; oppdagelsesreiser; polarområdene

Norway in the Antarctic - Brekke, Annemor (Ministry of Foreign Affairs, 1993)
Keywords: Antarktis; Antarktistraktaten; Norge; ekspedisjoner; forskning; hvalfangst; miljø

The regulation of Antarctic tourism: a study in regime effectiveness - Herr, Richard A; Davis, Bruce W (Fridtjof Nansen institutt, 1993)
Keywords: Antarktis; forvaltning; turisme

Environmental radioactivity in the Arctic and Antarctic - Holm, Elis (red.); Strand, Per (red.) (Scientific Committee of the International Conference on Environmental Radioactivity in the Arctic and Antarctic, 1993)
Keywords: Antarktis; miljøforurensing; polarområdene; radioaktivitet

Chilean Antarctic policy: the influence of domestic and foreign policy - Infante, Maria Teresa (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; politikk

The place of regulation in relation to science - Orheim, Olav (Changing trends in Antarctic research, 1993)
Keywords: Antarktis; miljø; miljøkonsekvensanalyser; miljøpåvirkning

The effectiveness of the Convention on the Conservation of Antarctic Marine Living Resources - Stokke, Olav Schram (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus; miljøvern

Antarctic tourism: a challenge to the legitimacy of the Antarctic treaty system? - Vidas, Davor (German yearbook of international law, 1993)
Keywords: Antarktis; jus; turisme

The Antarctic Treaty System and Antarctic tourism: towards a legal regime? (background information paper) - Vidas, Davor (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus; politikk; turisme

The Antarctic Treaty System and the law of the sea: a new dimension introduced by the 1991 Madrid protocol - Vidas, Davor (Fridtjof Nansens institutt, 1993)
Keywords: Antarktis; jus

Den Norske Sydpol-ekspedisjonen 1990-91 (Polarboken, 1992)
Keywords: Antarktis; ekspedisjoner

Executive summary: November 1992 (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; litteratur; politikk

ATS decision-making and change: the role of domestic politics in Australia - Davis, Bruce W; Herr, Richard A (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; politikk

The climate of Halley, Antarctica - Hanssen-Bauer, Inger; DNMI (Det norske meteorologiske institutt, 1992)
Keywords: Antarktis; klima; meteorologi

Antarctica and non-state actors: the question of legitimacy - Herr, Richard A; Davis, Bruce W (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; politikk

Into the heart of the Antarctic - Imbert, Bertrand C (North Pole, South Pole : journeys to the ends of the earth, 1992)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

The role of domestic politics in making United States Antarctic policy - Joyner, Christopher C (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; politikk

Activities within the Aurora Programme field season 1991/92 - Kristensen, Monica (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Antarktis; ekspedisjoner; glasiologi; meteorologi

Negotiating the mineral regime in the Antarctic: a review - Mørkved, Berit (International Challenges, 1992)
Keywords: Antarktis; jus; mineraler; politikk

The protection of the Antarctic environment - Orrego Vicuña, Francisco (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; miljøvern

Pertusaria signyae (Lichenes), a new species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A saxicolous Pertusaria species is described as new to science: P. signyae Ovst. from South Orkney Islands. It has an isidiate thallus, subglobose fertile verrucae with poriform apothecia, and contains 2'-0-methylperlatolic acid.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

Contributions to the Caloplaca flora of the western Antarctic region - Søchting, Ulrik; Øvstedal, Dag Olav (Nordic Journal of Botany, 1992)
Fourteen species of the lichen genus Caloplaca are recorded from the western Antarctic region and described morphologically and anatomically, viz.: C. ammiospila, C. approximata, C. athallina, C. cirrochrooides, C. citrina, C. isidioclada, C. lucens, C. millegrana, C. regalis, C. sublobulata, C. tenuis, C. aff. anchon-phoeniceon. Type specimens of critical species have been studied. A key is provided to the species. Caloplaca ammiospila and C. approximata are reported as new to the Antarctic region.
Keywords: Antarktis; botanikk; lav; planter

Domestic politics and non-state actors in the Antarctic Treaty System: towards a framework - Stokke, Olav Schram (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; politikk

Protecting the frozen south - Stokke, Olav Schram (Green globe yearbook, 1992)
Keywords: Antarktis; jus; miljøvern; politikk

Eine neue Gyalecta-Art aus der Antarctis: G. pezizoides sp. n. (lichensierte Fungi, Gyalectaceae) - Vezda, A.; Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A new species of the genus Gyalecta, G. pezizoides sp. n. (lichenized Fungi, Gyalectaceae), is described and illustrated. This new species is taxonomically near to the holarctic Gyalecta peziza (Mont.) Anzi.
Keywords: Antarktis; botanikk; lav; planter

Antarctic tourism: a challenge to the legitimacy of the Antarctic Treaty System? - Vidas, Davor (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; turisme

The Antarctic treaty system in world politics - Jørgensen-Dahl, Arnfinn (Red.); Østreng, Willy (Red.) (Macmillan in association with The Fridtjof Nansen Institute, 1991)
Keywords: Antarktis; Antarktistraktaten; forvaltning; havrett; internasjonalt samarbeid; miljø; naturressurser; polarområdene; politikk; ressurser; rett

Crustal development: Weddel Sea - Ross Sea region. Evolution of the Gondwana plate boundary in the Weddel Sea area - Kristoffersen, Yngve; Hinz, Karl (Geological evolution of Antarctica : proceedings of the Fifth International Symposium on Antarctic Earth Sciences, held at Robinson College, Cambridge, 23-28 August 1987, 1991)
Keywords: Antarktis; Weddellhavet; geofysikk; geologi; seismologi; tektonikk

Perspektiver for norsk forskning i Antarktis : langtidsplan for norsk Antarktis-forskning, høringsutkast av kapittel 6: framtidig norsk forskning - Omholt, Anders; Nygard, Jarle (Nasjonal komite for miljøvernforskning, NAVF, 1991)
Keywords: Antarktis; Norge; glasiologi; klima; marinøkologi; miljøforskning; polarforskning; polarområdene

The Eleventh Antarctic Treaty Consultative Meeting - Scully, Richard Tucker (International Challenges, 1991)
Keywords: Antarktis; jus; politikk

Stepwise Consolidation of Glacigenic Sediments Related to the Glacial History of Prydz Bay, East Antarctica - Solheim, Anders; Forsberg, Carl; Pittenger, Alan (Proceedings of the Ocean Drilling Program, 1991)
Keywords: Antarktis; glasiologi; isshelf; kontinentalsokkel

Adaptations to alpine and polar environments in insects and other terrestrial arthropods - Sømme, Lauritz; Block, William (Insects at low temperature, 1991)
Keywords: Antarktis; ekspedisjoner; insekter; kuldetoleranse; polarområdene; virvelløse dyr

Symposium report: "The Antarctic Treaty System in World Politics" - Stokke, Olav Schram (International Challenges, 1991)
Keywords: Antarktis; Sørishavet; forvaltning; jus; politikk

Vurdering av turisme i tilknytning til nordisk forskningsekspedisjon til Antarktis 1992/93 - Widmark, Eva Marie; Jørstad, Knut (Norsk Polarinstitutt, 1991)
Keywords: Antarktis; ekspedisjoner; forskning; turisme

Nankyoku ten - Amundsen, Roald; Nakada, Osamu (Dorufin Press, 1990)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Negtiationg a new regime: how CRAMRA came into existence - Andersen, Rolf Trolle (International Challenges, 1990)
Keywords: Antarktis; forvaltning; historie; mineraler; politikk

Protection of the environment in Antarctica: are present regimes sufficient? - Barnes, James N (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern

Antarctica's cultural heritage: can ICOMOS help? - Barr, Susan (Icomos information, 1990)
Keywords: Antarktis; Sørishavet; historie; kulturminneforvaltning

The resource conventions implemented: the consequences for the sovereignty issue - Beck, Peter J (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

Consultative status under the Antarctic Treaty: redefining the criteria? - Bos, Adrian (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The design of CRAMRA: how appropriate for the protection of the environment? - Brown, Alan D (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern; mineraler

The Antarctic in world politics - Dumas, Roland (International Challenges, 1990)
Keywords: Antarktis; politikk

Antarctica Treaty System: are there viable alternatives? - Falk, Richard (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The ability of the Antarctic Treaty System to adapt to external challenges - Haron, Mohamed (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

The influence of the United Nations on the Antarctic system: a source of erosion or cohesion? - Harris, Stuart (International Challenges, 1990)
Keywords: Antarktis; forvaltning; politikk

Høyest oppe, lengst borte: Mt. Vinson, 5200 m, høyeste fjell i Antarktis - Høibakk, Ralph (Polarboken, 1990)
Keywords: Antarktis; ekspedisjoner; fjellklatring

Antarctic science in a historical perspective: changing roles and functional development - Indreeide, Thor Vidar (International Challenges, 1990)
Keywords: Antarktis; forskning; historie; vitenskap

The legitimacy of the ATS - Jørgensen-Dahl, Arnfinn (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

CRAMRA: the ugly duckling of the Antarctic Treaty System? - Joyner, Christopher C (International Challenges, 1990)
Keywords: Antarktis; forvaltning; miljøvern; mineraler

CRAMRA and other enviromental regimes in the ATS: how well does CRAMRA fit? - Kimball, Lee A (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus; miljøvern

Towards firmer institutionalization of the ATS? Future role of the consultative meeting and the issue of a permanent secretariat - Messer, Kurt (International Challenges, 1990)
Keywords: Antarktis; forvaltning; jus

Veien til CRAMRA: en studie av forhandlingene om opprettelsen av et mineralregime i Antarktis - Mørkved, Berit (Fridtjof Nansens institutt, 1990)
Keywords: Antarktis; forvaltning; mineraler; politikk

SCAR in the ATS: conflict or harmony? - Rinaldi, Carlos (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning; politikk

The relationship between the ATS and the LOS convention of 1982 - Safronchuk, Vasiliy S (International Challenges, 1990)
Keywords: Antarktis; Sørishavet; havrett; jus; politikk

Resource management and the changing profile of science in Antarctica: a growing pressure for relevance? - Scully, Richard Tucker (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning

The relevance of the ATS as a model for international cooperation - Stokke, Olav Schram (International Challenges, 1990)
Keywords: Antarktis; jus; politikk

An Antarctic crossing as an analogue for long-term manned spaceflight - Ursin, Holger; Collet, Jérôme; Etienne, Jean L. (ESA Bulletin, 1990)
The long-duration space missions planned for the end of this century will involve both physiological and psychological problems for the crew who will fly them. If Europe is to achieve autonomy in space, it must increase its expertise in these associated disciplines. One means of acquiring relevant experience is to study human behaviour in environments that are similar from a psychological viewpoint. A planned crossing of the Antarctic by a six-man international team therefore offered ESA a unique opportunity to observe the psychological problems that can occur during an international expedition involving prolonged isolation in a hostile environment.
Keywords: Antarktis; fysiologi; psykologi

The unfinished task: CRAMRA and the question of liability - Wolfrum, Rüdiger (International Challenges, 1990)
Keywords: Antarktis; jus; mineraler